Effects of a personalized or generic three-dimensional tumoral kidney model on patient experience and caregiver-patient interactions, before and after partial nephrectomy, a randomized trial (Rein 3D Print Personalize-UroCCR 114). - Maxime Pattou; Sarah Masanet; Marthe-Aline Jutand; Hélène Hoarau; Joffrey Sarrazin; Alice Pitout; Laura Richert; Hugo Larribere; Federico Rubat Baleuri; Manon Jaffredo; Solène Ricard; Matthieu Faessel; et al. (PLoS ONE)
Introduction Personalized 3D-printed kidney models could serve as valuable educational tools for patients undergoing robot-assisted partial nephrectomy (RAPN). These models facilitate patients' understanding of their pathology, surgical procedure, and anatomy. However, the costs associated with 'personalized' printing remain a barrier to their use. This study aims to thoroughly investigate the benefits of using a personalized 3D-printed kidney model as opposed to a generic 3D-printed kidney model as an educational tool for patients and as a communication tool for healthcare professionals. Methods and analysis In this prospective single center study, 60 patients undergoing RAPN will be randomized to receive information based on their personalized 3D-printed tumoral kidney model or a generic 3D-printed tumoral kidney model. These models will accompany patients throughout their care pathway, from pre-operative consultations to the post-operative visit. The impact of these models on the management approaches of various healthcare professionals will also be examined. The data will be collected and analyzed using a mixed method, combining interviews (with patients and caregivers), observations during the presentation of the models and questionnaires (understanding of their pathology and the surgical procedure, Health-literacy, satisfaction). Discussion Three dimensional kidney models have the potential to play a central role in the preoperative information process and serve as an effective educational tool during the patient's social interactions with relatives and healthcare professionals. This study will evaluate the potential advantages of personalized 3D models of tumoral kidneys compared to their generic counterparts. Trial registration The PERSONALIZE study was registered on ClinicalTrials.gov (NCT06379698) on the 5th of September 2023.